Evaluating CNN and Vvsion transformer models for Mango Leaf variety identification - Labiba, Zaima; Heram, Afrin A; Hossain, Md.Muhtasim; Alam, Sharia; Shakal, Binita Khan (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.